Spain : Financial Sector Assessment Program -Technical Note; Regulation, Supervision, and Governance of the Spanish Cajas. (IMF Staff Country Reports; Country Report ;, 2006)
This report provides the background on the financial liberalization and deregulation process with special reference to Spain's cajas de ahorros (savings banks). It provides an overview of the cajas' governance structure and analyzes the regulation and supervision of cajas, with particular reference to the division of responsibilities between the central government (State) and the autonomous communities. It discusses the main challenges in terms of ensuring the cajas' operational autonomy and leveling between savings and commercial banks. It also summarizes the main findings and provides recommendations.